Protecting us from the pandemic? Reframing the work of security officers in quarantine hotels in Australia. (3rd July 2022) - Smith, Erica
ABSTRACT: This article examines the work and training of security officers employed by private security organisations for COVID-19 hotel quarantine contracts in Victoria, Australia. It reports on research fieldwork in the work of security officers and on analysis of training for the occupation. In March 2020, the occupation moved into the national spotlight, as the COVID-19 pandemic led to the use of hotel quarantine in Australia for travellers arriving from overseas. The employment conditions of, and inadequate training for, quarantine hotel security staff were found to be major contributors to a major COVID outbreak from July to September 2020. The article examines these developments in the light of the research findings about the nature of the security industry, particularly outsourcing and contracting issues, and the historic undervaluing of the work undertaken by security staff. These topics are especially important as security officers are increasingly used to support public security and safety.